Optimizing Google Classroom, Google Form and Zoom in Arabic Learning at Al-Azhar Islamic Boarding School Yogyakarta - Prastiwi, Arum Triasning; Masruroh, Dewi; Rumbaroa, Reza Hasbullah (Departemen Pendidikan Bahasa Arab, 2021)
Nowadays, educational facilities continue to experience improvements in the realm of technology. Various instant applications were created to facilitate the achievement of educational success. Therefore, every government, educational institution, educator, and student must master the technology so as not to be left behind. This research is qualitative descriptive research, the data collection techniques are observation, interviews and documentation conducted at al-Azhar Yogyakarta Boarding School. This study aims to determine the optimization of the use of Zoom, Google Classroom, and Google Form in learning Arabic. The results of this study: first, the learning phase begins with learning preparation which includes making a syllabus, selecting teachers, and making Google Classroom (importing material). Second, the implementation stage of learning is in accordance with the schedule that has been prepared with a Zoom explanation. The third is the implementation of the test as a benchmark for ongoing learning, starting with compiling questions written in the Google Forms, determining the time of the exam and assessment.